Differentiated Science Student Worksheets : What is the Level of Collaboration Skills of Students of the Elementary School Teacher Education Study Program? - Wahyu Kurniawati; Urmila Umardianti; Rahma Kurnia Novitasari; Anisya Al Husna (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to develop content-differentiated science student worksheets for students of the elementary school teacher education study program, especially on the subject of the human respiratory system, and analyze its effect on student collaboration skills. This research method used research and development with the 4D model (define, design, development, and dissemination). The sample in this study was 142 2nd semester students of elementary school teacher education study program at PGRI University Yogyakarta. The data was taken through student worksheets documentation, score lists, interviews, observations, validation assessment scales, and student collaboration skills questionnaires. The data analysis technique in this study used qualitative descriptive analysis techniques. Based on the research results, the student worksheets products that have been developed meet the validity criteria with an overall average of 97% in the very valid category. The validity and reliability results of the student collaboration skills questionnaire for the student worksheets developed have met the valid and reliable criteria. The results of the student collaboration skills trial given to 142 students on the developed student worksheets were the order of the number of students who always carried out collaboration skills starting from the responsible aspect (79%), the respect aspect (77%), the productive work aspect (71 %), aspects show flexibility (71%), and aspects contribute actively (38%). Meanwhile, the average number of students is 22% of students at a good level in collaborating and 78% of students are very good at collaborating.